Usulan Perencanaan Tata Letak Gudang Bahan Penolong Menggunakan Metode Class Based Storage di PT. XXX - Muhammad Hadziqul Afkar; Rr Rochmoeljati (Jurnal Serambi Engineering, 2025)
Warehouses play an important role in the logistics management of manufacturing companies, especially in supporting the smooth production process of PT. XXX, as the most complete fertilizer manufacturer in Indonesia. There are problems regarding the management of auxiliary materials warehouse, such as overstocking of some materials and sub-optimal warehouse layout. The purpose of this research is to optimise the warehouse layout of auxiliary materials at PT XXX by using the class-based storage (CBS) method and the fast moving, slow moving and non-moving (FSN) classification approach. The research method includes primary data collection through observation and interviews, as well as secondary data from the company's warehouse management system and references. According to the FSN analysis, there are three fast moving materials, seven slow moving materials and two non-moving materials. The layout optimisation results show that the main fast-moving materials increased by 10%, Al(OH)3 by 13% and Rough Jumbo Dolomite by 71%. In addition, non-moving materials such as acid clay and ferrous sulphate were removed, reducing the capacity of red clay by 64%. In this way, the class-based storage approach allows warehouse management to be more structured, efficient and responsive to operational needs.